Web-based Product Marketing Information System for MSMEs Tanggulangin Wallet and Bag Manufacturers: Sistem Informasi Pemasaran Produk Berbasis Web Pada UMKM Pengerajin Dompet dan Tas Tanggulangin - Dewi, Enda Nuriya; Sumarno, Sumarno (Universitas Muhammadiyah Sidoarjo, 2023)
The existence of MSMEs has an influence on improving people's welfare which can provide many business opportunities for the community. However, MSMEs currently have weaknesses in marketing their products, moreover they are still carrying out a manual marketing strategy using the method of making brochures, pamphlets and promoting their products in several stores. At the present time it is not easy to do marketing, the lack of the role of internet technology which can hinder MSMEs in terms of marketing their products. So that the business can develop and get maximum results, of course the role of internet technology is also very important for MSMEs in developing their business products. One way is to build an information system with PHP and MySQL programming as database storage. The end result of this research is the advantage of an information system that is useful for the long term with the aim of facilitating online marketing and sales to be able to expand market reach.